THE INFLUENCE OF COMMUNICATION ON EMPLOYEE PERFORMANCE PT HERONA EXPRESS SOUTH TANGERANG - Muhamad Ridwan (JURNAL ASIK, 2024)
The purpose of this research is to determine Communication on Employee Performance at PT Herona Express Tangerang Selatan. The research method used in this research is descriptive with a quantitative approach. The sampling technique used saturated samples so that the number of samples in this study was 50 respondents. Data analysis technique using multiple regression. The research results show that: There is a positive and significant influence of the Communication variable on the employee performance of PT Herona Express Tangerang Selatan. This is proven by the value of tcount > ttable, namely 5.394 > 2.010 with a probability value (significance) = 0.000, which is below 0.05.